Bioequivalence and Food Effect Assessment of 2 Fixed‐Dose Combination Formulations of Dolutegravir and Lamivudine. Issue 2 (14th November 2019) - Dumitrescu, Teodora Pene; Peddiraju, Kavita; Fu, Caifeng; Bakshi, Kalpana; Yu, Shui; Zhang, Zhiping; Tenorio, Allan R.; Spancake, Chris; Joshi, Shashidhar; Wolstenholme, Allen; Adkison, Kimberly
Abstract: This single‐dose study evaluated the bioequivalence, food effect, and safety of 2 experimental, 2‐drug, fixed‐dose formulations of 50 mg dolutegravir and 300 mg lamivudine (formulation AH and formulation AK) as compared with coadministration of single‐entity tablets of 50 mg dolutegravir and 300 mg lamivudine (reference). In fasted subjects, formulation AH lamivudine exposure was similar to the reference; however, dolutegravir exposure was consistently higher in formulation AH, with area under the concentration‐time curve (AUC) and maximum concentration (Cmax ) approximately 27% to 28% greater than reference. Formulation AK met bioequivalence standards to the reference for dolutegravir (AUC0‐∞ and Cmax ) and lamivudine (AUC0‐∞ and AUC0‐t ) exposure; however, dolutegravir AUC0‐t and lamivudine Cmax were approximately 16% and 32% higher than the reference, respectively. A high‐fat meal increased dolutegravir AUC and Cmax by up to 33% and 21%, respectively, and decreased lamivudine Cmax by approximately 30%. Both test and reference formulations were well tolerated. The results support further development of formulation AK as a novel, 2‐drug, fixed‐dose combination tablet treatment for patients with HIV.